A fatal case of fulminant group: a streptococcal infection in a neonate - Fumiko Satoh; Wataru Irie; Chizuko Sasaki; Eriko Ochiai; Maho Kondo (Egyptian Journal of Forensic Sciences, 2023)
Abstract Background Fulminant hemolytic streptococcal infection is a condition of sudden onset and rapidly progressing septic shock caused by Streptococcus pyogenes. It causes beta (complete) hemolysis. Although type A Streptococcus occurs more frequently, all streptococci that cause beta-hemolysis are eligible as causes. This report describes a rare autopsy case of fulminant group A streptococcal infection in a neonate. Case presentation A 16-day-old girl, 3300 g, born by spontaneous delivery at 41 weeks 1 day, experienced a 1-day history of low-grade fever, malaise, and a few hours of cyanosis and anuria, prompting her parents to bring her to the hospital. Her eldest brother, who lived with her, had been infected with Streptococcus approximately one month earlier, and had been treated with ten days of antibiotics. The infant died three hours after presentation. Autopsy findings indicated her to be 52 cm in length, weighing 3585 g, with medium build and normal nutrition. Her lungs were slightly oligemic with decreased volumes. The liver and kidneys were mildly enlarged. The spleen was markedly enlarged. The adrenal glands showed diffuse cortical hemorrhage (Fig. 1). There was some thymic atrophy (thymus weight 7.4 g, < 1 SD below the mean). Histopathological findings included chronic and neutrophilic infiltration of the tonsils and multiple septic emboli containing cocci in the lungs. Perivascular inflammatory cell infiltrates were observed in the lungs, myocardium, kidneys, adrenal glands, brain, meninges, and liver, with micro-necrotic changes in the kidneys and liver. Fibrin thrombi were observed in multiple renal glomeruli. Hemophagocytosis by macrophages was observed in the spleen, liver, lymph nodes, bone marrow, and adrenal glands. Immunostaining showed positive results for group A Streptococcus antibody in the tonsils, with bacterial masses. Blood cultures were positive for group A Streptococcus pyogenes. Conclusions Because of the lower respiratory tract infection and suspected sibling transmission, in addition to the adrenal hemorrhages, a diagnosis of fulminant sepsis with group A Streptococcus pyogenes with associated Waterhouse–Friderichsen syndrome was made.